KEPATUHAN DIET PASIEN DABETES MELITUS - Geneo, Martinus; Ake, Julianus; Alabimbang, Abriyanti (Lasalle Health Journal, 2023)
Introduction: Diabetes mellitus is a chronic disease that can have a bad impact on sufferers. One way that can help patients with diabetes mellitus to maintain a good quality of life is to carry out diet therapy. Objective: To find out whether age, education and family support are factors that cause diabetes mellitus sufferers to be non-compliant with their diet. Method: In this research, quantitative research was used using a cross sectional approach. The population in the study were patients suffering from diabetes mellitus in Teling Bawah Village, Wenang District, Manado City, North Sulawesi with a total of 45 respondents. Sampling was the entire population, namely 45 respondents. Results: From this study, results were obtained which showed that there was a significant relationship between family support and dietary compliance in diabetes mellitus patients based on the results of the Spearman rho test, which obtained a p-value of 0.002 (α=0.05). For age and education level, there is no significant relationship with diet compliance in diabetes mellitus patients. For age the p-value is 0.199 (α=0.05), and for education level the p-value is 0.076 (α=0.05). Conclusion: There is a significant relationship between family support and dietary compliance in diabetes mellitus patients, there is no significant relationship between age and dietary compliance in diabetes mellitus patients, there is no significant relationship between education level and diet compliance in diabetes mellitus patients